thanks!!

### 2 Answers

lim((x,y)→(0,0)) (cos(xy) – 1)/(x^2 y^2)

= lim(t→0) (cos(t) – 1)/t^2, letting t = xy

= lim(t→0) (cos(t) – 1)(cos(t) + 1) / [t^2(cos(t) + 1)]

= lim(t→0) (cos^2(t) – 1) / [t^2(cos(t) + 1)]

= lim(t→0) -sin^2(t) / [t^2(cos(t) + 1)]

= lim(t→0) (sin(t)/t)^2 * [-1/(1 + cos t)]

= 1^2 * -1/2

= -1/2.

I hope this helps!

The limit is -1/2. If you take x = r cosΘ and y = r sinΘ, then for r near zero,

cos(xy) = 1 – ½(r^4 cos²Θ sin²Θ) + 1/24 r^8 cos^4Θ sin^4Θ + …

so that

(cos(xy) – 1)/(x²y²) = – 1/2 + O(r^4)

(That is standard big-oh notation on the right.)